Invective as a lyrical genre: the semantic structure (based on Russian and Polish poetry of 19th –20th centuries) - Краковяк, Александра (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article presents a study on invective as a lyrical genre from the point of view of its semantic structure, based on samples of the genre identified in Russian and Polish poetry of 19th–20th centuries. Comparative analysis of texts facilitated an emergence and description of stable semantic structure, which is a unique one amongst other genres. This confirms status of invective as an independent literature genre and contributes to the building of a model of a genre process.